Analysis of Youth Morality in Realizing Character-Based Education - Ponnui, Putri Munira; Maifizar, Arfriani (LPPM Universitas Negeri Jakarta, 2025)
Character education plays a crucial role in shaping a high-quality young generation with a strong national identity in the modern era. This article discusses the urgency of character education in the context of national development, with a focus on itsimplementation in the Indonesian education curriculum. Through literature review and conceptual analysis, this study reveals that character education not only helps prevent negative behaviors such as corruption and intolerance but also contributes to improving quality of life and developing students’ potential. Character education must besystematically and comprehensively integrated into all aspects of education, whether in schools, families, or communities. Therefore, character education becomes a solid foundation in creating a young generation that is not only intellectually capable but also possesses integrity, responsibility, and the ability to contribute positively to society. The conclusion of this article emphasizes that character education is a top priority in national development and must be implemented with full commitment from all stakeholders.